Enterococcus faecalis sir2‐like gene enhances aerobic metabolism of themselves and mitochondrial respiration of mammal cells to bring about improving metabolic syndrome through the PGC‐1α pathway. (22nd January 2019) - Li, Shiyu; Fei, Zhengbin; Xu, Zhenrui; Wang, Jiajia; Jiang, Zhenyou; Xie, Yajie; Wang, Yuzhe; Huang, Wenhua; Sun, Hanxiao
Abstract: Recent studies showed that probiotics could improve metabolic syndrome, making the identification of factors affecting metabolic control more important than ever. The mammalian sirtuin protein family has received much attention for its regulatory role, especially in various mitochondrial ATP, glucose, and lipid metabolic pathways. However, compared with the mammalian sirtuin protein family, the function of prokaryotic sir2 protein is much less known. We studied the effects of probiotics sir2 protein on cell energy metabolize pathway, which showed that deletion of Enterococcus faecalis sir2 inhibited the aerobic oxidation of bacteria and increased the bacterial fermentation. The study of EF‐sir2 (sir2 protein of E . faecalis ) role of molecular targets demonstrated that deacetylation of EF‐sir2 was via Rho upregulating in E . faecalis . When transfected into HEK293T cells, EF‐sir2 could significantly facilitate aerobic oxidation of glucose, enhance the respiration to generate more ATP, and cause upregulation of NRF1 target gene. Then, we found EF‐sir2 could increase activity of PGC‐1α by deacetylation and PGC‐1α inhibition decreased the expression of NRF1 target gene. Finally, we demonstrated that EF‐sir2 could significantly improve the metabolic index of mammalian cells through insulin resistanced model in vitro and metabolic syndrome rat model in vivo. Our results first revealed that prokaryotic sir2 genes affect the molecular mechanism of cellular metabolism and the regulatory of cell homeostasis in prokaryotic and mammalian cells, suggesting that EF‐sir2 has a positive regulatory effect on metabolic disturbance and may be used for the prevention and treatment of pathological processes related to metabolic syndrome.